Detection of lithium in scalp hair by time-of-flight secondary ion mass spectrometry with high energy (MeV) primary ions. Issue 36 (18th August 2017) - Cloete, Karen J.; Jenčič, Boštjan; Šmit, Žiga; Kelemen, Mitja; Mkentane, Kwezikazi; Pelicon, Primož
Abstract : The application of MeV-SIMS is presented for the detection and mapping of lithium in chemically unprocessed, longitudinally sectioned scalp hair. Abstract : In this exploratory study, the application of secondary ion mass spectrometry with a heavy primary ion beam with an energy of several MeVs (MeV-SIMS) is presented for the simultaneous detection and spatial distribution mapping of lithium in a single, chemically unprocessed strand of scalp hair across a longitudinal profile.